(untitled) (Economic and Political Thought, 2010)
The aim of the publication is to analyze and assess changes that have taken place in the Polish transport since the early 1990s. They involved the transport industry in the field of its structure and ownership, leading to the increase of the number of companies in every branch of transport as well as the development of the private sector. They were also connected with the role of transport in the Polish economy and the structure of haulage. Due to a weaker dynamics of development than in other branches and the change of the structure of the size of businesses, the employment in transport decreased and its position measured as a share in the WDB weakened. The process of integration and liberalization of the transport market, against predictions, did not weaken the dynamics of Polish transport companies, especially those involved in road transport. Road transport became the most important branch of the business with a market share of 70% of the transport of goods. Road transport companies also took full advantage of the possibilities arising from the membership in the uniform market of the European Union.